Effect of leaching on lime stabilised contaminated soil and mining waste - Musta, Baba (2003)
Degradation of environment due to industrial and mining related activities is identified as one of the major problem facing by most industrial and developing countries. Therefore, scientific research are needed to acquire knowledge to manage such toxic waste, which has a potential to degrade on the environment as well as on human health. Leaching column tests were conducted on two soil samples and one mining waste sample in order to investigate the potential of lime stabilisation technique to immobilise heavy metals. The soil samples were obtained fiom Kg. Kayumadang, Telipok, Sabah (KMT) and Kg. Bongkud, Ranau, Sabah (KGB), whereas the mining waste was obtained from Lohan Dam, Ranau, Sabah (LDA). The amounts of lime used for the stabilisation were 2%, 4%, 6%, and 8% of dry weight. Five selected heavy metals namely Cu, Cr, Ni, Pb, and Zn were chosen to understand their behavioural changes with the long term leaching process. These heavy metals were spiked into the unstabilised and lime stabilised samples in the leaching columns. The pH values of leachate from all stabilised KMT, KGB, and LDA samples were found to be alkaline, indicating that the heavy metals were adsorbed on the surface of the cementitious minerals, whilst the Ca ions were released from the cementitious compound. The trend of migration profiles showed that the concentrations of the heavy metals decreased with depth for all samples. On the other hand, very low concentrations of heavy metals were detected in the leachate of the lime stabilised samples. Mass balance calculations showed that Zn had the highest mobility in KMT sample, whereas Ni was the highest in KGB and LDA samples, Calculations also showed that Pb was the least mobile in KMT, whereas Cr was the slowest in both KGB and LDA samples. The permeability of all stabilised samples decreased significantly immediately after leaching processes due to the clogging of pore by fine materials and the development of cementitious mineral. Scanning electron microscope (SEM) study showed that the bottom part of the leached columns had tights structure with low pore spaces, which were clogged-up by fine materials. Using X-ray diffraction (XRD) technique, quartz, kaolinite, feldspar and cementitious minerals were detected in the stabilised samples. Nevertheless, SEM method illustrated better image of the cementitious mineral. Soil classification tests, chemical characterisations, mineralogical identifications, and engineering properties verification were also performed on both unstabilised and stabilised samples to examine the liming effect on their properties. Maximum unconfined compressive strength (UCS) was achieved by adding 6% lime to the KMT, KGB, and LDA samples, and this strength increased with age. Based on the leaching column and UCS tests, 6% lime is suggested as the optimum value for stabilisation of KMT and KGB samples. Hence, lime stabilised KMT and KGB could be used as a clay liner due to their low permeability and high strength. It is also possible to stabilise LDA with 6% lime with the addition of fine material to facilitate stabilisation process, thus irnmobilising heavy metals within the stabilised mining waste.